The Murtad’s dilemma : the political, social and educational marginality of the Malay apostate in Singapore. - Muhammad Amin Abdul Rahim Abdullah. (2013)
Studies on the Malays in Singapore and their social, economic and political marginality have been well documented, as are its cultural ties with Islam. The perception of the Singaporean Malay as a Muslim is a unique characteristic when compared to other races in Singapore. This portrayal disregards the minority of Malays who are not Muslim. In this paper, I shall delve into the myth of a homogenous Malay Muslim community by studying the Murtads, apostates who have rejected the religion of their birth, exploring their life stories, and experiences. I will document how the State, media, its institutions and community co-operate in formalizing this dominant discourse, and in doing so, marginalize the individuals who do not fit within this group’s self-identity.